The 37-year kidney transplantation experience at Siriraj Hospital. - N. Premasathian (2018)
With 37-years of experience, a total of 801 kidney transplantations (59.4% were deceased donors and 40.6% were living donors) performed at Siriraj hospital were reported. The point system parallel to OPTN/UNOS for waitlists was utilized. Most of the recipients of deceased donor kidney transplantations had 3 HLA mismatches. Due to the point allocation system, none of them had 6 HLA mismatches. Extended criteria donor comprised 7.8% of all deceased donors. Mean duration of dialysis prior to deceased donor transplant was 53 +/- 34 months. Delayed graft function (DGF) was found in 54% of deceased donor kidney transplantation and resulted in significantly higher rate of 1 year biopsy-proven acute rejection, longer duration of kidney transplant admission, higher admission cost and lower patient survival compared to those with immediate graft function. Most of living donor kidney transplant recipient had 1 haplotype match. Mean donor age was 35.9 +/- 9.8 years. 95.6% of the recipients were on hemodialysis prior to transplantation. The current standard regimen includes calcineurin inhibitor, Mycophenolic acid and prednisolone. Interleukin-2 receptor monoclonal antibody has been used in the high immunological risk or high risk for DGF recipients that were 50% of the recipients. There was no statistically significant difference in the biopsy-proven acute rejection (BPAR) free survival between deceased and living donor transplantation. Proportion of cases with the diagnosis of acute rejection according to Banff 2007 classification is as follows: 32.4% acute cellular rejection (ACR), 39.4% antibody-mediated rejection (AMR) and 21.1% mixed cellular and antibody-mediated rejection. Seventy two patients, 35 deceased donor and 37 living donor kidney transplant recipients, had biopsy-proven glomerular disease after transplantation which IgA nephropathy is the most common form of glomerulonephritis. Median graft survival was 7.6 and 13.2 years and median patient survival was 12.1 and 15.5 years for recipient of deceased and living donor transplant respectively. The follow up program of living donors was introduced in 2003 and there were not any donors who required renal replacement therapy.